Efficient Molecular Marker Design Using the MaizeGDB Mo17 SNPs and Indels Track. Issue 6 (1st June 2014) - Settles, A Mark; Bagadion, Alyssa M; Bai, Fang; Zhang, Junya; Barron, Brady; Leach, Kristen; Mudunkothge, Janaki S; Hoffner, Cassandra; Bihmidine, Saadia; Finefield, Erin; Hibbard, Jaime; Dieter, Emily; et al.
Abstract: Positional cloning in maize ( Zea mays ) requires development of markers in the region of interest. We found that primers designed to amplify annotated insertion–deletion polymorphisms of seven base pairs or greater between B73 and Mo17 produce polymorphic markers at a 97% frequency with 49% of the products showing co-dominant fragment length polymorphisms. When the same polymorphisms are used to develop markers for B73 and W22 or Mo17 and W22 mapping populations, 22% and 31% of markers are co-dominant, respectively. There are 38, 223 Indel polymorphisms that can be converted to markers providing high-density coverage throughout the maize genome. This strategy significantly increases the efficiency of marker development for fine-mapping in maize.